Pengaruh Kompetensi Perangkat Desa Dan Penerapan SISKEUDES Terhadap Kualitas Laporan Dana Desa - Raidah Adillah; Rahma Nazilla Muhammad; Arif Apriady (Indonesian Accounting Research Journal, 2021)
According to the BPKP (Financial and Development Audit Agency) there are two factors that affect the quality of village fund reports, namely competent human resources and adequate information technology. This study aims to determine the effect of village apparatus competence and the application of SISKEUDES on village fund financial reports. This research is descriptive quantitative and conducted in the Village District Arjasari, Bandung Regency. The sampling method used was non-probability sampling with purposive sampling technique. The research respondents were 77 people. The data collection method used was a questionnaire, and the data were processed using multiple linear regression analysis. The results showed that the competence of village employees and the implementation of the village financial system had a partial and simultaneous positive effect on the financial statements of village funds in eleven villages in Arjasari Sub- District.